The influence of physical exercise on college students’ life satisfaction: The chain mediating role of self-control and psychological distress - Zhou, Guang-Yu; Yang, Bin; Li, Hao; Feng, Quan-Sheng; Chen, Wan-Yi (Frontiers in Psychology, 2023)
Objective: To explore the influence of college students’ daily physical exercise on life satisfaction and the dual role of self-control and psychological testing between them. Methods: 526 college students were tested by Physical Index Scale, Life Satisfaction Scale, Self-control Scale, and Psychological Distress Scale. Results: 1) Physical exercise was positively correlated with life satisfaction (r = 0.09, P < 0.05) and self-control (r = 0.20, P < 0.01), and negatively correlated with psychological distress (r = -0.14, P < 0.01). Life satisfaction was positively correlated with self-control (r = 0.43, P < 0.01) and negatively correlated with psychological distress (r = -0.40, P < 0.01). Psychological distress was negatively associated with self-control (r = -0.52, P < 0.01). 2) Mediation model testing reveals that psychological exercise cannot affect life satisfaction (β = -0.01, p > 0.05). However, it can indirectly influence satisfaction through the college students’ mediated effects of self-control (β = 0.06, Fig. p < 0.05) and the chain mediating effect of self-control and psychological distress (β = 0.03, p < 0.05). Conclusion Physical exercise can improve the self-control ability of college students to reduce psychological distress and ultimately lead to an improvement in life satisfaction.